Pemanfaatan Konsumsi Jambu Biji Merah Dalam Upaya Menurunkan Kadar Asam Urat Pada Lansia Di Kecamatan Karang Ampel Indramayu - Pipin Supenah; Muhammad Ibnu Ubaidillah; Fiki Setiawan; Ikhwani Ikhwani; Oktafirani Al Sas; Novita Novita (BADAN PENERBIT STIEPARI PRESS, 2022)
Gout often attacks at the age of > 45 years because at that age estrogen levels decrease, causing an increase in uric acid in the blood. Hyperuricemia can be overcome with herbal treatment in the form of consuming guava juice because it contains vitamin C which has a uricogenic effect, namely increasing the body's uric acid excretion, thereby reducing the formation of uric crystals in the blood. The purpose of this community service is to increase public knowledge about the benefits of guava fruit in reducing uric acid levels. This service is carried out through counseling activities and giving guava fruits to increase public knowledge and understanding of the importance of consuming guava fruits in reducing uric acid levels. The method used in this activity was counseling by means of socialization first and then followed by observation using questionnaires and blood sampling for gout examination in the elderly as many as 22 people in Karangampel Indramayu District on May 9 - 20, 2022. The results and conclusions of this activity are that guava can reduce uric acid levels in the elderly in Karangampel Indramayu District.